Manajemen Brand Image-Concept AQUA Sebagai Brand Bijak Berplastik Melalui Produk AQUA Life - Astrid Eveline; Hanny Hafiar; Priyo Subekti (Jurnal Nomosleca, 2020)
This study titled "AQUA Brand Image-Concept Management as a Bijak Berplastik Brand through AQUA Life Product" is a descriptive study with qualitative data type that focuses on knowing AQUA Brand Image-Concept Management as a Bijak Berplastik Brand through AQUA Life product. This study aims to answer questions regarding; 1) step of Consumer Needs Matching, 2) step of Identify Potential Brand Image, 3) step of Identify the Brand Concept, and 4) step of Selecting Brand Image-Concept Strategy on Brand Image-Concept Management as a Bijak Berplastik Brand through AQUA Life product. Data collection techniques used included interviews with eight key informants, non-participatory observation, and literature study. Technical validity of the data using source triangulation. The results of this study revealed that; 1) AQUA has carried out ideal consumer matching needs, but can still be optimized by categorizing products, segmenting benefits, and current needs of consumers that are done more specifically, 2) AQUA is still not optimal in identifying potential brand images, where AQUA has not done the verification process data in market research, 3) AQUA is still not optimal in identifying brand concepts, namely in mapping experiential abstractions delivered to consumers through AQUA Life products, 4) AQUA is still not optimal in selecting potential brand image-concepts, that is, it has not distributed its products to all distribution channels where product availability has an influence on buying interest and attractiveness of consumers to the desired product AQUA Life can form the brand image of AQUA as a Bijak Berplastik brand. Keywords: brand image management; brand concept; brand image-concept; AQUA Life Keywords: brand image management; brand concept; brand image-concept; AQUA Life